Vocabulary Mastery and Cognitive Strategies Used by EFL Students in Process-Based Learning - Daristin, Pipit Ertika (PPPM STIT MIFTAHUL MIDAD, 2025)
This study aims to explore vocabulary mastery and cognitive strategies used by EFL students in process-based learning. Employing a qualitative research design, the study involved fourth-semester students of the English Education Department at University of Hasyim Asy’ari, Jombang. Data were collected through classroom observations, semi-structured interviews, and document analysis to gain an in-depth understanding of how students utilize vocabulary knowledge and apply cognitive strategies during learning processes. The findings reveal that vocabulary mastery plays a crucial role in supporting students’ comprehension and engagement in process-based learning activities. Students employed various cognitive strategies, including repetition, inference, elaboration, and monitoring, to construct meaning and manage learning tasks effectively. Moreover, the use of process-based learning encouraged students to become more aware of their vocabulary use and strategic thinking. This study highlights the importance of integrating vocabulary development with cognitive strategy instruction to enhance meaningful learning experiences for EFL students in higher education contexts.